2018
DOI: 10.1021/acsami.8b13140
|View full text |Cite
|
Sign up to set email alerts
|

Sub-2 V, Transfer-Stamped Organic/Inorganic Complementary Inverters Based on Electrolyte-Gated Transistors

Abstract: Organic/inorganic hybrid complementary inverters operating at low voltages (1 V or less) were fabricated by transfer-stamping organic p-type poly(3-hexylthiophene) (P3HT) and inorganic n-type zinc oxide (ZnO) electrolytegated transistors (EGTs). A semicrystalline homopolymerbased gel electrolyte, or an ionogel, was also transfer-stamped on the semiconductors for use as a high-capacitance gate insulator. For the ionogel stamping, the thermoreversible crystallization of phase-separated homopolymer crystals, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Following the previous reports in the literature, the displacement current with various sweep rates was measured and n i was calculated from y -intercept of (∫ I Disp d V G )/( er V A ) versus r V –1 plot (Figure S9). We found n i in the range of 10 14 –10 15 cm –2 , which is close to the values in the reports of ionogel-gated OEGTs. ,, We also found that n i increased after chemical dedoping, following the trend in the MISM capacitance. PEDOT:PSS exhibited the largest degree of increase in n i from 1.5 × 10 14 to 1.1 × 10 15 cm –2 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Following the previous reports in the literature, the displacement current with various sweep rates was measured and n i was calculated from y -intercept of (∫ I Disp d V G )/( er V A ) versus r V –1 plot (Figure S9). We found n i in the range of 10 14 –10 15 cm –2 , which is close to the values in the reports of ionogel-gated OEGTs. ,, We also found that n i increased after chemical dedoping, following the trend in the MISM capacitance. PEDOT:PSS exhibited the largest degree of increase in n i from 1.5 × 10 14 to 1.1 × 10 15 cm –2 .…”
Section: Resultssupporting
confidence: 90%
“…13 We found n i in the range of 10 14 −10 15 cm −2 , which is close to the values in the reports of ionogel-gated OEGTs. 14,35,65 We also found that n i increased after chemical dedoping, following the trend in the MISM capacitance. PEDOT:PSS exhibited the largest degree of increase in n i from 1.5 × 10 14 to 1.1 × 10 15 cm −2 .…”
Section: Resultssupporting
confidence: 62%
“…The statistical data (trip voltages, gains, and noise margins) shown in Figure demonstrated good uniformity of printed hybrid CMOS inverters. Compared with other hybrid CMOS inverters based on metal oxide, SWCNT TFTs, and organic TFTs shown in Table 2 , the hybrid CMOS inverter in this work demonstrates the highest voltage gain, largest noise margin, and lowest static power consumption at the supply voltage of 2 V …”
Section: Resultsmentioning
confidence: 91%
“…Recently, hybrid CMOS inverters based on the combination of different channel materials, such as organic/metal oxides, quantum dots/SWCNTs, 2D materials/SWCNTs, and metal oxides/SWCNTs, have been demonstrated. A few studies have studied the fabrication of TFTs by combining n‐type metal oxides and p‐type SWCNTs; however, their performance is still not satisfied with relatively low voltage gains and small noise margins at operation voltages less than 2 V. The key reason is that the performance characteristics of printed p‐type and n‐type transistors, i.e., mobility, sub‐threshold swing (SS), threshold voltage, and operation voltage, usually do not match well .…”
Section: Introductionmentioning
confidence: 99%
“…6a). In addition to existing OECT technologies, we have also compared our results with voltage amplifiers based on electrolytegated thin-film transistors [28][29][30][31] and organic field-effect transistors [32][33][34][35][36] (details can be found in Supplementary Table 2). Cutting-edge voltage amplifiers, that implement unipolar organic field-effect transistors in differential 36 and pseudo-CMOS 35 37 where the power supply is heavily limited.…”
Section: Printed Oect-based Push-pull Voltage Amplifiersmentioning
confidence: 99%